Intra-family relations and the residents of Pertubuhan Kebajikan Warga Tua Nurul Saadah Terengganu: guiding principles from Qur'anic perspective - Wan Mohd Nasir, Wan Hazwani; Fatah Yasin, Raudlotul Firdaus (IIUM Press, International Islamic University Malaysia, 2017)
Elderly care centres primarily emphasise social and personal requirements of senior citizens. The number of elderly people being sent to elderly care centres in Malaysia have increased due to the rapid growth of the elderly population. Regrettably, a significant number of problems have been identified among the residents at these centres. Among the problems include children’s refusal to take care of their elderly parents because of their limited abilities, time constraint, financial and health problems, as well as sheer abandonment and negligence of responsibilities by their own children and next of kin. These problems are closely related to the intra-family relationship of the residents and have been identified as one of the contributing factors of the abandonment and mistreatment of some elderly residents admitted to elderly care centres. Fundamentally, Islam stresses the rights of parents to be treated with kindness, obedience, and honour as mentioned in the Qur’an (Al-Isra’ 23-24), and in the hadith, the Prophet SAW reprimanded that disobedience to parents to be one of the seven major sins. With respect to this issue, this study attempts to propose Quranic guiding principles in highlighting the roles and responsibilities of children towards their parents in elderly care centres by focusing on the residents of Persatuan Kebajikan Warga Tua Nurul Saadah, (PKWTNS), Jerteh, Terengganu as a case study. The study will employ inductive method, observation and interviews as the main methods for completing the study. The study proposes the solutions from three dimensions, which is from the individual, society as well as from the institutional reform. In addition, this study also proposes a Quranic guideline to highlight the roles and responsibilities of children towards their parents at elderly care centres.